T.O. Selfridge papers - Selfridge, T. O. (Thomas Oliver), 1836-1924.
Correspondence, journals, logbooks, notebooks, scrapbooks, maps, drawings, and other papers relating primarily to Selfridge's command of survey expeditions to the Isthmus of Darien (Panama) as a site for an interoceanic canal in the 1870s. Includes material relating to the sinking of the USF Cumberland (Frigate) by the CSS Merrimack (Frigate) in 1862, the purchase of the John T. Pickett papers (Confederate States of America records) in Canada in 1872 by the United States, and Selfridge's court-martial in 1888. Correspondents include Daniel Ammen, J.P. Benjamin, Edward Knight Collins, George Davidson, W.W. Evans, Gustavus Vasa Fox, James Bicheno Francis, John B. Jervis, Benjamin Henry Latrobe, Benjamin Peirce, John L. Porter, Thomas Oliver Selfridge, Sr., and J. Dutton Steele.
Naval officer and explorer.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Forms part of: Naval Historical Foundation collection.
Keywords: Ammen, Daniel, -- 1820-1898 -- Correspondence; Benjamin, J. P. -- 1811-1884 -- Correspondence; Collins, Edward Knight, -- 1802-1878.; Davidson, George, -- 1825-1911 -- Correspondence; Evans, W. W. -- 1817-1886 -- Correspondence; Fox, Gustavus Vasa, -- 1821-1883 -- Correspondence; Francis, James Bicheno, -- 1815-1892 -- Correspondence; Jervis, John B. -- 1795-1885 -- Correspondence; Latrobe, Benjamin Henry, -- 1806-1878 -- Correspondence; Peirce, Benjamin, -- 1809-1880 -- Correspondence; Pickett, John T. -- 1822-1884.; Porter, John L. -- 1813-1893 -- Correspondence; Selfridge, Thomas Oliver, -- 1804-1902 -- Correspondence; Steele, J. Dutton -- 1810-1886 -- Correspondence; Confederate States of America; Confederate States of America. -- Navy; Cumberland (Frigate); Merrimack (Frigate); Canals; Surveys -- Panama -- Panama, Isthmus of; Darien (Panama and Colombia) -- Description and travel; Panama, Isthmus of (Panama) -- Discovery and exploration; Panama Canal (Panama); United States -- History -- Civil War, 1861-1865 -- Naval operations; Explorers; Naval officers